Evaluasi Metode Value For Money Dalam Penggunaan Dana Desa : Studi Pada Desa Bua' Tarrung Kabupaten Tana Toraja - Darmawati; Nirwana; olyvia melky yanti (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This study aims to evaluate the management of Dana Lembang in Bua’ Tarrung using the Value for Money approach, which encompasses the aspects of economy, efficiency, and effectiveness. A quantitative method was employed by analyzing secondary data from the regional budget reports (APBD) and budget realization from 2022 to 2024. The findings indicate that the economic aspect of Dana Lembang management is categorized as good, with an average expenditure realization of 92.97%. Efficiency is reflected in the frugal use of funds without compromising the achievement of planned outputs. In terms of effectiveness, program implementation demonstrated a high level of alignment between budget allocation and outcomes, with realization rates ranging from 89.90% to 97.30%. These results suggest that the Value for Money principles have been consistently applied, although there remains room for improvement, particularly in strengthening budget efficiency. This study offers practical contributions by recommending enhanced transparency in planning, reinforced internal control, and increased community involvement as strategies to sustainably optimize the management of Dana Lembang.